2017
DOI: 10.1111/jam.13557
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of carvacrol for control of avian aspergillosis in intratracheally challenged chickens in comparison to voriconazole with a reference on economic impact

Abstract: Prognosis of avian aspergillosis is often poor due to delayed diagnosis and treatment failure. However, the widespread uses of azole prophylaxis in birds are thought to be the major driver of azole resistance. These findings create a possibility to develop an effective drug-free alternative strategy for control of avian aspergillosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
(95 reference statements)
2
7
0
Order By: Relevance
“…In vitro sensitivity of our fungal isolates to 5 antifungal drugs showed that A.Fumigatus isolates showed 100 %resistant to Fluconazole, 67% resistant to both Nystatin and Amphotericin B while 50 % resistant to Itraconazole and only sensitive to Ketoconazole with 67%. Our results agreed to some extend with those reported by Ziółkowska et al (2014) and Tartor and Hassan (2017) in case of Fluconazole, Amphotericin B and Itraconazole, except in case of ketoconazole who found that most strain of A.fumigatus was resistant to it.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In vitro sensitivity of our fungal isolates to 5 antifungal drugs showed that A.Fumigatus isolates showed 100 %resistant to Fluconazole, 67% resistant to both Nystatin and Amphotericin B while 50 % resistant to Itraconazole and only sensitive to Ketoconazole with 67%. Our results agreed to some extend with those reported by Ziółkowska et al (2014) and Tartor and Hassan (2017) in case of Fluconazole, Amphotericin B and Itraconazole, except in case of ketoconazole who found that most strain of A.fumigatus was resistant to it.…”
Section: Discussionsupporting
confidence: 93%
“…Garlic oil has moderate activity (10 ±1 mm), thyme oil and chamomile oil did not exhibit any antifungal sensitivity for A.fumigatus isolates. These results were in agreement with that reported by Singh et al (1995); Inouye et al (2000); Carmo et al (2008);Rana et al (2011);Srivastava (2015) and Tartor and Hassan (2017).…”
Section: Discussionsupporting
confidence: 93%
“…Consequently, oral antimycotics are preferred and various approaches such as nebulization or the use of nanosuspensions have been attempted ( Wlaź et al, 2015 ; Pardeike et al, 2016 ). Since therapeutic protocols have not been validated specifically for birds in general and for the various species in particular, necessary care should be taken, especially considering the prolonged time required to complete the treatment ( Tartor and Hassan, 2017 ). In cases in which anesthesia is necessary such as surgery for air sac exposure to alleviate respiratory distress or imaging tests, the eventual impact of air way obstructions or other lung lesions upon the anesthetic process must be considered.…”
Section: Veterinary Infections Caused By Aspergillus mentioning
confidence: 99%
“…Carvacrol is an essential oil from the oregano plant with in vitro antifungal activity against a variety of fungal species (42,(53)(54)(55)(56) and has been shown to have potential in vivo application as a prophylactic agent for the prevention of avian aspergillosis (57). Although the precise molecular target of carvacrol is unknown, its ability to disrupt ER morphology and induce a UPR transcriptional signature in C. albicans clearly indicates that it causes acute ER stress (42).…”
Section: Discussionmentioning
confidence: 99%